MQTT and CoAP Communication Protocol Analysis in Internet of Things System for Strawberry Hydroponic Plants - Nilam Andi Safitri; Ardy Seto Priambodo (Journal of Robotics, Automation, and Electronics Engineering, 2023)
Strawberry is a fruit that is widely consumed and cultivated globally because of its richness in nutrients, vitamins, and minerals. However, several challenging factors that need to be faced in strawberry cultivation are temperature, humidity, lighting, etc. The author focuses on the application of IoT in container strawberries, especially in high-temperature advertisements. Where Hardware, Back End and Front End are important frameworks for developing the system. In developing a system that utilizes IoT technology optimally andefficiently, it is necessary to consider the lines of communication. Without an eligible communication, the device cannot be connected smoothly. In thisstudy the authors will focus on Back End to analyze the performance of the two protocols MQTT and CoAP. The MQTT protocol is better used for IoT-based hydroponic plant automation systems because the MQTT protocol can configure messages/packets sent. MQTT can provide efficient and reliable communications in the IoT environment. In addition, the development of the prototype of strawberry cultivation using the container aims toallow strawberry farmers to control the plants without having to be near the plants.